PERAN DAN KEKUATAN PEMBUKTIAN KETERANGAN AHLI BAGI TERDAKWA YANG SEDANG MENJALANI PEMULIHAN MEDIS (PUTUSAN NOMOR 1050/PID.SUS/2022/PN DPS): The Role and Evidentiary Strenght of Expert Testimony for Defendants Undergoing Medical Recovery (Court Decision No.1050/Pid.Sus/2022/PN Dps) - Syahran Meizar Abdullah; Wangga, Maria Silvya Elisabeth (Reformasi Hukum Trisakti, 2026)
Narcotics abuse is a complex legal problem because on the one hand it is seen as a criminal act, but on the other hand, narcotics can also be used for medical recovery purposes as regulated in Law Number 35 of 2009 concerning Narcotics. The difference between the use of narcotics in the context of medical recovery and the illegal abuse of narcotics often does not receive adequate attention in judicial practice, especially in the evidentiary mechanism in trial. The formulation of the problem raised in this study is "What is the strength of the evidence of expert testimony in the Denpasar District Court Decision Number 1050/Pid.Sus/2022/PN Dps?" This study uses a normative legal research type with a descriptive nature. Data analysis was conducted qualitatively with deductive conclusions drawn. The results of the discussion and conclusions indicate that expert testimony in this case has valid, formal evidentiary power. The use of drugs included in certain categories should be accompanied by a letter or official document proving that the person concerned has permission to use the drugs. The absence of this document demonstrates the importance of expert testimony in providing evidentiary power, particularly in assessing whether the act constitutes drug abuse